2005
DOI: 10.1063/1.1874301
|View full text |Cite
|
Sign up to set email alerts
|

Interface characterization of nanoscale laminate structures on dense dielectric substrates by x-ray reflectivity

Abstract: On nanoscale laminate structures, the interface cannot be identified any longer as the separation between two films of bulk materials. The formation of the interface defines the final composition and structure of the laminate structure. As such, the characterization of the interface becomes an important challenge. In this work the nanoscale laminate structures were formed by atomic layer deposition (ALD) of tungsten nitride carbide and tantalum nitride thin films on dense dielectrics [silicon carbide and silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Using the PDMAT precursor with NH 3 in a thermal ALD process, Travaly et al observed that the high-resistivity Ta 3 N 5 phase was deposited. 19 Ritala et al showed that the reducing power of NH 3 is indeed insufficient and thermal ALD using TaCl 5 precursor resulted in the deposition of the Ta 3 N 5 phase. 10 They reported that they could only deposit conductive TaN x films by thermal ALD when applying additional zinc dosing during the NH 3 exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Using the PDMAT precursor with NH 3 in a thermal ALD process, Travaly et al observed that the high-resistivity Ta 3 N 5 phase was deposited. 19 Ritala et al showed that the reducing power of NH 3 is indeed insufficient and thermal ALD using TaCl 5 precursor resulted in the deposition of the Ta 3 N 5 phase. 10 They reported that they could only deposit conductive TaN x films by thermal ALD when applying additional zinc dosing during the NH 3 exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for applications relying on interface properties or based on a nanolaminate stack of films, the oxidation or nitridation of the underlying material during film growth could affect the aimed device structure and, thereby, deteriorate the device performance. 10,18 Because ellipsometry is sensitive to the optical constants of a material, it can be used to monitor the formation of an interfacial film given that the optical contrast between the different layers is sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] When reducing the film dimensions towards the nanometer scale, detailed insight into aspects such as finite size effects, film nucleation, and interface formation/modification becomes essential. [8][9][10][11] Therefore, successful application of ultrathin films in devices has to be accompanied by accurate metrology techniques to determine the properties of these thin films. The films are mostly studied by ex situ diagnostics giving detailed insight into the thin film properties, however, at the cost of time-consuming and often sample-destructive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine-containing molecules, by-products of WF 6 reactions, etch SiO 2 as showed the lower density SiO 2 substrate after exposure to WF 6 . 35 Furthermore, the material primarily formed at the interface is a tungsten nitride material ͑Fig. 5͒ suggesting good compatibility with nitrogen-containing surfaces.…”
Section: Resultsmentioning
confidence: 99%